Targeted dementia screening performance, its barriers and associated factors among primary care doctors at public primary healthcare clinics in Malaysia - Suluraju, Chitra; Sazlina, Shariff-Ghazali (Universiti Putra Malaysia, 2024)
Introduction: Targeted dementia screening is recommended for early recognition of dementia. However, many persons with dementia were not identified and managed in timely manner. This study aimed to determine the proportion of performing targeted dementia screening, its barriers and associated factors among primary care doctors in public primary healthcare clinics. Methods: A cross sectional study was conducted at 4 public healthcare clinics, Putrajaya from December 2018 – February 2019. All primary care doctors who fulfilled the eligibility criteria were recruited. We collected data using a pre-tested self-administrated questionnaire comprised socio-demographic, medical information, healthcare experience and training, knowledge on dementia, awareness of dementia screening tool availability and barriers to dementia screening. The outcome was the performance of targeted dementia screening. Descriptive, Chi-square and independent t-test analyses were performed. Results: A total of 106 primary care doctors participated in this study. The proportion of primary care doctors who performed targeted dementia screening was 11.3%. Most participants were family medicine trainee (42.9%), with duration of service between 5 and 10 years (15.0%), had professional caring experience of dementia patients (21.4%), and had undergone dementia training (36.2%). Many of the participants perceived barriers to perform targeted dementia screening that included lack of time (72.6%) and lack of knowledge (59. 4%). Conclusion: The prevalence of performing targeted dementia screening was low with modifiable barriers. Strategies to improve the performance of targeted screening such as creating awareness among primary care doctors could be done for a start.